214 Severe traffic accidents in southern finland 2006–2015 as seen from level 1 trauma centre. (1st September 2016) - Handolin, Lauri; Söderlund, Tim; Brinck, Tuomas
Abstract : Session has four presentations on different types of severe traffic accidents: pedestrian, motor vehicle, motor bike, and bicycle accidents. Helsinki University Hospital trauma unit (Töölö hospital) is a tertiary trauma centre providing trauma care in severe injuries for Helsinki and its quite densely populated surroundings, resulting in a catchment area of nearly 2 million people (about 35% of the total Finnish population). The total number of annual ISS >15 (severe trauma) trauma patents in Töölö hospital is around 450. Töölö hospital's trauma registry was established in 2006. All trauma admissions to Töölö hospital have been reviewed by three trauma nurses and all patients with NISS (New Injury Severity Score) over 15 have been included in the registry. The data input includes demographic, process mapping, and outcome data. The registry data collected 2006–2015 on severe traffic accidents is presented in this session focusing in patient demographics, injury mechanisms and patterns, severity of injuries, outcome, and changes in incidences during past decade in the Southern Finland.